The effect of pomegranate mouthrinse on Streptococcus mutans count and salivary pH: An in vivo study - Dilshad Umar; Bahija Dilshad; Mohammed Farhan; Arshiya Ali; Kusai Baroudi (Wolters Kluwer Medknow Publications, 2016)
Herbal mouthwashes have been considered to be a more advantageous option to their chemical counterparts, for a long-time. The use of pomegranate fruit dates from ancient times and reports of its therapeutic abilities have echoed throughout the ages. To evaluate the effect on the salivary pH and the Streptococcus mutans count in healthy subjects before and after pomegranate mouthrinse. Fifty healthy patients were randomly divided into two groups of 25 subjects each. Group A was treated with 0.2% chlorhexidine mouthrinse; while Group B was treated with pomegranate peel extract (PPE) mouthrinse and the saliva samples were collected at three different intervals: Prerinse, after 10 min, and 60 min. The salivary pH was measured using a digital pH meter and the S. mutans count was determined by the commercial system Dentocult SM. The statistical analyses used in this study are Mann-Whitney U-test and t-test. PPE mouthrinse had an inhibitory effect on S. mutans count in adults. There was also an increase in the salivary pH after 10 min of the mouthrinse. PPE mouthrinse may be considered as a potential anticariogenic mouthrinse.